2019
DOI: 10.1002/pbc.27834
|View full text |Cite
|
Sign up to set email alerts
|

Mucormycosis diagnosed during induction chemotherapy in five pediatric patients with acute lymphoblastic leukemia

Abstract: Mucormycosis in pediatric oncology patients is a rare invasive fungal infection associated with significant morbidity and mortality. We describe five patients diagnosed with mucormycosis during induction chemotherapy for acute lymphoblastic leukemia at our institution. All of the patients in our series survived, some in spite of having disseminated disease. Most of the patients’ chemotherapy was modified with the aim of controlling their leukemia while minimizing immunosuppression until their fungal infection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 19 publications
2
12
0
Order By: Relevance
“…In the literature review, a mucormycosis-related mortality of 36.5% was observed. 5,[7][8][9]14,[17][18][19][20] These mortality rates are in accordance with the previous mucormycosis review of this subgroup in which a mortality of 36.1% was reported from 1990 to 2007 (without significant trend in survival over time) (n = 61). 17 As described, our review strengthens the concept that survival has significantly improved over time.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In the literature review, a mucormycosis-related mortality of 36.5% was observed. 5,[7][8][9]14,[17][18][19][20] These mortality rates are in accordance with the previous mucormycosis review of this subgroup in which a mortality of 36.1% was reported from 1990 to 2007 (without significant trend in survival over time) (n = 61). 17 As described, our review strengthens the concept that survival has significantly improved over time.…”
Section: Discussionsupporting
confidence: 92%
“…17 In the literature review, all series but one reported the highest incidence of mucormycosis during induction therapy, which is in line with our case series. 5,8,9,14,17–20…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Children with hematological malignancies undergoing chemotherapy treatments involving immunity are among the highest-risk groups. When the index of suspicion is low, this diagnosis can go unnoticed, which has severe consequences since the mortality rate in patients who develop the disseminated disease can be as high as 100% [1][2][3] .…”
Section: Introductionmentioning
confidence: 99%